Parallel p-adic method for solving linear systems of equations - Koç, Ç.K. (Parallel computing, 1997)
We present a parallel algorithm for an exact solution of an integer linear system of equations using the single modulus p-adic expansion technique. More specifically, we parallelize an algorithm of Dixon, and present our implementation results on a distributed-memory multiprocessor. The parallel algorithm presented here can be used together with the multiple moduli algorithms and parallel Chinese remainder algorithms for fast computation of the exact solution of a system of linear equations with integer entries.